URGENSI PENDIDIKAN NILAI DI ERA DIGITALISASI - Muhammad Alfi Syahrin (LPPM STAI Muhammadiyah Probolinggo, 2023)
In the current era of global development of information technology, the position of valueseducation is very central because it is in a position that is needed to be able to give meaning to each material subject to deliver the Indonesian nation towards an advanced civilization. The purpose of this article is to develop the concept of the importance of value education in dealing with conditions of global technological progress. This study uses the concept of library research for the urgency of the importance of values education. The results of the conceptual arrangement show that the use of technology needs to be balanced with value education so that the values and personality of the Indonesian nation remain intact and maintained. If the inculcation of values in education at this time is not strengthened, it is not impossible that the Indonesian people will gradually lose their identity and will not be able to maintain their national identity because they are easily influenced by global foreign cultures. So it can be concluded that technological progress needs to be strengthened by value education as a filter so that students are able to be critical in reasoning and moral considerations and able to choose good and correct values based on foundation, religion, ethics, morals and norms that apply in IndonesiaKeyword : Value Education, Digitalization, Moral Degradation